ANALISIS PREFERENSI KONSUMEN TERHADAP GULA SEMUT AREN DI PULAU LOMBOK - Selamet, Ario Jamari; Budastra, I Ketut; Efendy, Efendy (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
This study aims to: (1) Describe consumer buying behavior towards Crystals Palm Sugar from point of purchase, purchase frequency, purchase amount and purchase purposes on Lombok Island, (2) Analyze consumer preferences on Crystals Palm Sugar attributes on Lombok Island. The method used is the descriptive method. The unit of analysis in this study was the consumers of crystals palm sugar on the island of Lombok. Determination of the sample area using purposive sampling with the consideration that West Lombok Regency is an crystals palm sugar production location and sale location and the city of Mataram is a crystals palm sugar production retail outlet. The number of respondents in this study was 50 respondents that were determined by the accidental sampling technique. The types of data used are qualitative data and quantitative data. The data sources used are primary data and secondary data. The data analysis used was an interval scale evaluation and it was processed by conjoint analysis with the help of the SPSS version 25 application. The results of this study indicate that: (1) The purchasing behavior of crystals palm sugar consumers in Lombok Island is that they prefer to buy at the production site, twice a month, the number of purchases is > 1000 gr in a month, and the purpose of the purchase is for consumption. (2) Crystals palm sugar attributes that are consumer preferences based on utility value are original flavor 0.095, IDR15,000-IDR25,000 price 0.357, permanent bag packaging type 0.180, BPOM label 0.590, halal label 0.855, and 1000gr size 0 .332. The crystals palm sugyar attributes that respondents considered the most when choosing crystal palm sugar on Lombok Island in sequence, starting from most considered to least considered, were halal label value 23,599, price 21,068, BPOM label value 17,002, packaging type value 16,511, size value 14,601, and last one is the aroma attribute with an importance value of 7.219.